Development of functional liposomes by modification of stimuli-responsive materials and their biomedical applications. Issue 6 (21st January 2020) - Yuba, Eiji
Abstract : The fabrication strategies and biomedical applications of stimuli-responsive material-modified liposomes are summarized and reviewed. Abstract : Liposomes are a promising nanocarrier for drug delivery because of their biocompatibility and the encapsulation capacity of drugs. Liposomes can be functionalized easily by introduction of functional materials such as stimulus-responsive materials. Temperature-responsive liposomes and pH-responsive liposomes are representative stimulus-responsive liposomes that can deliver drugs to locally heated target tissues and intracellular organelles. Here, temperature-responsive liposomes for the selective release of cargo and pH-responsive liposomes for the induction of antigen-specific immunity are overviewed. Temperature-responsive polymer-modified liposomes immediately released drugs in response to heating, which achieved selective drug release at a tumour after topical heating of tumour-bearing mice. Introduction of MR-detectable molecules enabled the tracing of liposome accumulation into target sites to optimize the heating timing. These liposomes can also be combined with magnetic nanoparticles or carbon nanomaterials to attain magnetic field-responsive, electric field-responsive and light-responsive properties to support on-demand drug release or control of biological reactions using these external stimuli. pH-Responsive liposomes were produced by modification of poly(carboxylic acid) derivatives or by pH-responsive amphiphiles. These liposomes delivered antigenic proteins into the cytosol of antigen presenting cells, which induced cross-presentation and antigen-specific cellular immunity. Adjuvant molecules or bioactive polysaccharide-based pH-responsive polymers improved their immunity-inducing effect further, leading to tumour regression in tumour-bearing mice. Precise design and control of the structures of stimulus-responsive materials and combination with functional materials are expected to create novel methodologies to control biological functions and to produce highly potent liposomal drugs that can achieve selective release of bioactive molecules.